2012
DOI: 10.5194/hess-16-4661-2012
|View full text |Cite
|
Sign up to set email alerts
|

Elevation correction of ERA-Interim temperature data in complex terrain

Abstract: Abstract. Air temperature controls a large variety of environmental processes, and is an essential input parameter for land surface models, for example in hydrology, ecology and climatology. However, meteorological networks, which can provide the necessary information, are commonly sparse in complex terrains, especially in high mountainous regions. In order to provide temperature data in an adequate temporal and spatial resolution for local scale applications a new elevation correction method has been develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
158
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 40 publications
11
158
0
Order By: Relevance
“…Modeled temperature is corrected with altitude according to the standard lapse rate (−6.5 K/km). Although more complex methods have shown improvements in coarser models (Gao et al 2012), comparison of different techniques at high resolution suggests that further correction is not needed .…”
Section: Observational Data and Model Assessment Metricsmentioning
confidence: 99%
“…Modeled temperature is corrected with altitude according to the standard lapse rate (−6.5 K/km). Although more complex methods have shown improvements in coarser models (Gao et al 2012), comparison of different techniques at high resolution suggests that further correction is not needed .…”
Section: Observational Data and Model Assessment Metricsmentioning
confidence: 99%
“…Previous studies have shown that the elevation difference between the reanalysis grid point and the corresponding 20 meteorological station leads to a large systematic bias (Gao et al, 2012(Gao et al, , 2014a(Gao et al, , 2016. Thus, the elevation correction scheme based on a lapse rate, which explains the empirical relationship between air temperature and altitude, can reduce this bias significantly.…”
mentioning
confidence: 99%
“…series is the prerequisite for accurate climate change assessment especially on a regional scale (Gao et al, 2012;Pepin and Seidel, 2005;Minder et al, 2010;Maurer et al, 2002;Mooney et al, 2011). However, as the most common sources for air temperature time series, observational networks suffer from the low-station density in complex terrains, in particular at high mountains (Gao et al, 2014a).…”
mentioning
confidence: 99%
See 2 more Smart Citations